Fuel Consumption Pattern by the Mechanized Fishing Sector in Andhra Pradesh - Gopal, Nikita; J., Charles Jeeva; G.R., Unnithan (Fishery Technology, 2025)
The study aims at ascertaining the fuel utilization pattern by different classes of mechanized fishing vessels in Andhra Pradesh. The estimate gives the consumption pattern of 7941 kL of diesel for small mechanized, 3818 kL for sona, 3684 kL for mini trawlers and 11256 kL for trawlers with the pooled estimate for Visakhapatnam district as a whole being 26699 kL for the year 2004. The consumption in Andhra Pradesh state was 19698 kL for small mechanized, 21744 kL for sona, 3684 kL for mini trawlers and 11256 kL for trawlers, the pooled estimate being 56382 kL. The average per day fuel utilization by different categories of crafts was 117.83 Its for small mechanized, 202.44 Its for sona, 502.54 Its for mini trawlers and 1173.26 Its for trawlers. Based on the ideal fishing trips that can be undertaken by different categories of crafts, it has been estimated that the mechanized sector as a whole has undertaken only 79.58% operation in Visakhapatnam and 79.7% in whole of Andhra Pradesh state during the year of study.